Applying the Problem-Based Learning Model to Computer Network Topics Through the Use of Video Media - Susiati Gea; Arini Vika Sari (Jurnal Pendidikan Vokasi Indonesia, 2025)
This study aims to describe the implementation of the Problem-Based Learning (PBL) model in teaching computer network topics using video media among eleventh-grade students at SMA Nasrani 3 Medan. The PBL model, which emphasizes learning through real-world problem-solving, is designed to foster students’ critical thinking, independence, and active engagement in the learning process. This research employed a classroom action research design, conducted in two cycles. Data were collected through questionnaires, interviews, and assessment sheets administered after the instructional sessions. The collected data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that the application of the PBL model supported by video media significantly enhanced students’ critical thinking skills and their ability to solve problems effectively. Thus, the PBL approach proves to be effective in improving both the learning process and outcomes in computer network instruction.